Water Ambulance Service Provision to Improve Healthcare Access for Community in Nusa Penida Island, Bali: A Qualitative Feasibility Study - Aryani, Putu; Harjana, Ngakan Putu Anom; Januraga, Pande Putu; Kurnianingsih, Desak Ketut Dewi Satiawati; Wirawan, Gede Benny Setia; Swapatni, Ni Made Adi; Wibawa, I Komang Gede Sentanu (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: An important component of healthcare access is transportation. Lack of transportation has been cited as an important barrier to healthcare access in remote islands region. Here we conduct a feasibility study on the implementation of water ambulance service to improve healthcare access in the region of Nusa Penida and its surrounding islands in Bali Province, Indonesia. Methods:  We employed a qualitative approach with interviews and focused group discussions with stakeholders. Data collection was conducted to assess the feasibility of operating water ambulance services, based on a framework that included technical, market, organizational, and financial feasibilities. Inductive coding was conducted and data was analyzed to evaluate the feasibility based on local capacity against pre-determined framework of assessment based in literature. Results: Qualitative interviews revealed perceived urgency and need for water ambulance service among stakeholders. They also perceive the need of water ambulance service was not mutually exclusive to other alternatives, such as expanding healthcare capacity on the islands. There was also readiness and adequate capacity from stakeholders which include a dedicated health emergency services under the health office that coordinate ambulance service in the region, readiness to create dedicated medical team and boat crew to operate water ambulance services, and readiness to cover the cost of initial procurement followed by operational costs which may include public-private partnerships. Conclusion: There was a strong perceived need for water ambulance service in Nusa Penida Islands. At the same time, local stakeholders revealed adequate basic capacity to feasibly operate water ambulance services according to benchmarks identified in literature review.